Realizacja programu reprywatyzacji w Republice Czeskiej i na Węgrzech po roku 1989 - Patkowski, Krzysztof (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2009)
The paper discusses Czech and Hungarian ideas concerning the implementation of the reprivatization program, which are compared with Polish reprivatization programs in the conclusion. In all these countries more or less successful attempts have been undertaken to solve the problem of returning property to former owners. Similar problems have been encountered everywhere, and it has been practically impossble to return to the original status quo. In each country a majority of large industrial plants have expanded. Ater the war numerous state investments carried out which have completely altered these businesses. At the same time, apartments which became state property at some time were being sold on a great scale.
The Implementation of the Reprivatization Program in the Czech Republic and Hungary following 1989